Early evidence of molariform hypsodonty in a Triassic stem-mammal - Melo, Tomaz Panceri (2019)
Hypsodonty, the occurrence of high-crowned teeth, is widespread among mammals with diets rich in abrasive material, such as plants or soil, because it increases the durability of dentitions against wear. Hypsodont postcanine teeth evolved independently in multiple mammalian lineages and in the closely related mammaliaforms since the Jurassic period. Here, we report the oldest record, to our knowledge, of hypsodont postcanines in the non-mammaliaform stem-mammal, Menadon besairiei, from the early Late Triassic. The postcanines are long and columnar, with open roots. They were not replaced in older individuals and remained functional after the total wear of the crown enamel. Dental histology suggests that, convergently to hypsodont mammals, wear was compensated by the prolonged growth of each postcanine, resulting in dentine hypsodont teeth most similar to extant xenarthran mammals. These findings highlight the constraints imposed by limited tooth replacement and tooth wear in the evolutionary trajectories of herbivorous mammals and stem-mammals.